A developmental approach to the patent-competition interface - Cheng, TK (2020)
This thesis proposes an approach to the patent-competition interface for developing countries. It puts forward a theoretical framework for the patent-competition interface for developing countries after canvassing relevant policy considerations. It examines the many reasons why patent protection is often not essential for generating innovation incentives in developing countries. These include the tendency of the patent system to overcompensate innovators, the availability of other appropriation mechanisms for innovators to monetize their innovations, and the lack of appropriate technological capacity in many developing countries to take advantage of the incentives generated by the patent system. It also argues that developing countries with a small population need not pay heed to the impact of their patent system on the incentives of foreign innovators. It then proposes a classification of developing countries into production countries, technology adaptation countries, and proto-innovation countries and argues that dynamic efficiency considerations take on different meanings for developing countries depending on their technological capacities. For the vast majority of developing countries bereft of meaningful innovation capacity, foreign technology transfer is the main vehicle for technological progress. The chief dynamic policy consideration for these countries is hence incentives for technology transfer instead of innovation incentives. There are three main means of voluntary technology transfer, importation of technological goods, foreign direct investment, and licensing. Competition law regulation of patent exploitation practices interacts with these three means of technology transfer in different ways and an appropriate approach to the patent-competition interface for these countries needs to take these into account. Distilling all these considerations, the thesis proposes an industry-specific approach to the patent-competition interface that is adjusted based on the country’s technological capacity. This approach is then applied to two patent exploitation practices, unilateral refusal to license and patent tying for illustration.